A Single-Switch AC/DC Flyback Converter Using a CCM/DCM Quasi-Active Power Factor Correction Front-End - Athab, Hussain S.; Lu, Dylan Dah-Chuan; Ramar, Krishnathevar (2012)
This paper discusses the major issues that exist in the single-stage ac/dc converters with power factor correction (PFC) and presents a novel converter based on a quasi-active PFC scheme. Two additional windings wound in the transformer of a conventional dc/dc flyback converter are used to drive and achieve continuous current mode operation of an input inductor. In addition, direct energy transfer paths are provided through the additional windings to improve the conversion efficiency and to reduce the dc bus capacitor voltage below 450 V for universal line applications. The proposed converter can be easily designed to comply with IEC 61000-3-2 Class D requirement and to achieve fast output voltage regulation. By properly tuning the converter parameters, a good tradeoff between efficiency, dc bus capacitor voltage stress, and harmonic content can be achieved. Operating principles, analysis, and experimental results of the proposed method are presented